Anthropometry of Indonesia agricultural workers of Java and Madura Tribes in East Java and its application in the design of agricultural tools - Wibowo, Robertoes Koekoeh Koentjoro; Soni, Peeyush; Athapol Noomhorm; Anal, Anil Kumar; Salokhe, Vilas M.; Jember Univerasity (Indonesia). Directorate General of Higher Education (Pathum Thani, Thailand : Asian Institute of Technology, 2014)
The study was conducted to obtain anthropometry data of Javanese and Madurese farmers in the three districts of Jember, Banyuwangi and Lumajang East Java, Indonesia for age groups of 16-67 years (males) and 15-59 years (females) respectively. Anthropometry data taken in this study included 58 body dimensions, age, body weight, and three indices, namely RSH, BSA, and BMI. Mean, SEM, CV, (SD), and percentile among body dimensions were considered. Three hundred and twenty one farmers were measured in this study. The eighty male and 85 female farmers from Javanese, and 76 male and 80 female farmers of Madurese tribes participated in this study. Results indicated that the anthropometric characteristics of Javanese and Madurese male farmers were significantly (p<0.05) different, mainly in their stature, eye height, Elbow height, fingertip height, knuckle height, wrist height, hip height, shoulder height, and some of body dimensions. The survey also revealed that the mean values of BSA, BMI and hand squeeze strength of Javanese male and female farmers were significantly (p<0.05) higher than the Madurese. The anthropometric measurements of Javanese farmers are mostly higher than that of Madurese farmers.
The isometric muscle strength of Javanese and Madurese farmers in East Java, Indonesia. The measurement was conducted on the hand grip, shoulder lifts, and torso pull strength in certain position. The correlation between isometric strength and selected anthropometric dimensions of Javanese and Madurese both male and female farmers is varied from -0.717 for correlation between age (years) with torso pull in bent position while palm facing down to 0.583 for correlation between stature and hand squeeze strength.
An intensive survey of 270 Javanese and 232 Madurese male and female farmers in the study area revealed that the farmers in East Java, Indonesia commonly use agricultural hand tools when farming. The popular agricultural hand tools are sickle (100.0%), hoe (92.0%), big/long knife (69.3%), shovel (23.5%), sprayer (19.1%), and harrow (16.5%). During farming, farmers suffer injury at their body; where they suffer most frequent injuries on hands (75.10%). Based on the Abbreviated Injury Scale (AIS), most of the farmers face injuries at minor to moderate levels. The significant correlation of hand injury with minor and moderate injury was 0.60 and 0.40, respectively. Hard material on the handle of the tools contributed as the highest influencing factor to farmers injury (44.68%). The feel of comfort and level of satisfaction to farmers in using agricultural hand tools greatly varied among different levels, which were used during farming activities. Correlation matrix was constructed between injury and comfort levels of the farmers. A significant correlation (-0.274) occurred between minor injury and comfort with hoe. Those who were comfortable to use hoe, were also comfortable with other hand tools (sickle, harrow, shovel, big/long knife, and sprayer) (p<0.05). From the correlation matrix between injury and satisfaction of the farmers it is evident that those who were not satisfied with hoe, harrow, shovel, and big/long knife-are the victims of minor or moderate injury (p<0.05).
By using PCA with varimax rotation, the first rank preference of farmers is safety for hand tools, and then followed by good fit in hand, easy to use, reliable and to no inflamed skin in the last. For agricultural hand tools, farmers prefer utilitarian performance than hedonic performance. In relation to body dimensions of the farmers in East Java, Indonesia it is therefore recommended to redesign the agricultural hand tools such as sickle and big/long iv knife. The ergonomic evaluation suggests their handle length and diameter to be 12.4 cm and 3.0 cm, respectively.
A dissertation submitted in partial fulfillment of the requirements for the degree of Doctor of Engineering in Agricultural Systems and Engineering, School of Environment, Resources and Development
Thesis (Ph.D.) - Asian Institute of Technology, 2014
Keywords: Anthropometry -- Indonesia; Agricultural machinery -- Design; Machine-tools -- Design